On the use of verlan to subtitle African American Vernacular English into French: transnational hybridity - Mevel, Pierre-Alexis (University of Bologna, 2014)
The polysemiotic nature of subtitled films, whereby textual information (the subtitles) is combined with other audiovisual cues (the pictures and the soundtrack of the film) makes them very vulnerable as a form of translation, as well as a peculiar one: a consequence of the process of subtitling is that both the original (or source text) and the translation (target text) are presented simultaneously to viewers. The possibility of clashes between source and target texts is therefore very great, and incoherencies produced by the juxtaposition of visual referents from the source-language cultural sphere alongside textual referents originating from the target language are often commented upon by translation specialists. Whilst it is widely admitted that the use of cultural substitution – that is when a cultural reference in the source-text is replaced by another one in the target language – in subtitles should be resorted to with extreme caution, a coherent and consistent approach is also absolutely paramount in order to maintain viewers’ suspension of disbelief throughout the film. Looking at a corpus of films from the 1990s portraying predominantly African American characters, this paper analyses the ways in which the dialogues have been subtitled into French. While in most films subtitles display a tendency to neutralise the non-standard features of the original, some also reveal a great level of inventiveness and creativity: the juxtaposition in the subtitled films of features that are culturally-bound (whether to the source or to the target culture) produces a hybrid. Whilst the use of non-standard features from the target language in the subtitles can be justified by connotations they have in common with African American Vernacular English, the use of such features is not unproblematic and raises important issues.